Royalty Mechanism under Government Regulation No. 56 of 2021 and the Fair Use Principle in Copyright - Immanuel Given Bintang Andhiyo; Dwi Desy Yayi Tarina (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
Government Regulation No. 56 of 2021 on the Management of Royalties for Copyrighted Songs and/or Music was enacted to safeguard the economic rights of creators through a centralized royalty management system administered by the National Collective Management Organization (LMKN). Existing studies on LMKN primarily emphasize institutional authority, collection mechanisms, and royalty distribution efficiency. This study offers a novel perspective by introducing and conceptualizing the dissenting right as a critical yet overlooked dimension within Indonesia’s royalty governance framework. This research argues that the flat-fee royalty mechanism mandated by the regulation produces substantive injustice by disregarding actual usage intensity and by coercively imposing royalties even where creators explicitly decline economic remuneration. Such practices undermine the individualized nature of copyright as a personal and proprietary right. Moreover, the extension of royalty obligations to commercial establishments where music serves merely as a supporting element, rather than a core commercial commodity, further disrupts the balance between copyright protection and public interest. Using a normative juridical approach, this study demonstrates that the absence of a dissenting right within the LMKN system reflects a structural imbalance that weakens creators’ autonomy over their own works. The research proposes the integration of the fair use principle as a complementary regulatory mechanism to operationalize the dissenting right, allowing limited non-prejudicial use of works without mandatory royalty payment. This integration constitutes the primary novelty of the study, offering an alternative regulatory model that is more proportional, creator-centered, and responsive to diverse modes of music utilization, while preserving equilibrium between economic rights protection and public access.